Wordwall Learning Media to Increase Student Concept Understanding in Islamic Age Education Lessons at SMK NU Al-Hidayah Ngimbang - Chotimah, Chusnul; A'isyaturrohmah, Ainin; Prihatiningtyas, Suci; Husna, Asiyah Lu'Lu'ul (LPPM Universitas KH. A. Wahab Hasbullah, 2025)
This study investigates the use of Wordwall as an interactive learning medium to enhance students’ conceptual understanding in Islamic Religious Education (PAI) at SMK NU Al-Hidayah Ngimbang. The research employs a quasi-experimental design with a one-group pretest-posttest approach, involving 30 eleventh-grade students. Data collection was conducted through pretest and posttest assessments to measure changes in conceptual understanding. Before using Wordwall, the average pretest score was 56.7, indicating low conceptual understanding. Following the integration of Wordwall, the average posttest score significantly increased to 86.7, with an average N-Gain of 0.66, categorized as medium. The interactive and gamified nature of Wordwall is attributed to this improvement, as it fosters student engagement and provides immediate feedback, supporting active learning. The findings highlight the potential of Wordwall to enhance learning outcomes in PAI by addressing students' diverse learning needs and improving motivation and comprehension. This study provides practical implications for educators seeking to implement innovative, technology-based learning solutions in vocational schools to improve conceptual understanding and align with the demands of 21st-century education.